Weak Semantics Based on Lighted Button Pressing Experiments. An Alternative Characterization of the Readiness Semantics - Ingólfsdóttir, Anna (BRICS Report Series, 1996)
Imposing certain restrictions on the transition system that defines the behaviour of a process allows us to characterize the readiness semantics of [OH86] by means of black-box testing experiments, or more precisely by lighted button testing experiments [BM92]. As divergence is considered we give the semantics as a preorder, the readiness preorder, which kernel coincides with the readiness equivalence of [OH86]. This leads to a bisimulation like characterization and a modal characterization of the semantics. A concrete language, recursive free CCS without tau, is introduced, a proof system defined and it is shown to be sound and complete with respect to the readiness preorder. In the completeness proof the modal characterization plays an important role as it allows us to prove algebraicity of the preorder purely operationally.